An Unusual Cervical Tumor as Presentation of a Non-Hodgkin Lymphoma - Tom De Greve; Lieve Vanwalleghem; Achiel Van Hoof; Kenneth Coenegrachts; Philippe Van Trappen (Hindawi Limited, 2014)
Rare cervical cancers are responsible for a minority of cases encountered by a clinician. However, behavioral patterns, management, and prognosis of certain rare cervical cancers differ from either squamous carcinomas or adenocarcinomas. Here we present a case of a locally advanced cervical tumor as a presentation of an extranodal cervical non-Hodgkin lymphoma (NHL), with a review of the current literature.